Study of Commercial Law (Economic Law) and Environmental Law related to Plastic Waste Import in Indonesia - Nomensen Freddy Siahaan; Agustina Wati (Journal of Social Research, 2026)
Effective waste management is essential for reducing Indonesia’s dependence on imported waste. However, inadequate domestic waste management systems have made it difficult for the country to meet industrial raw material needs independently. One of the industries significantly affected is the paper industry, which requires both long and short fibers for production. These materials are not solely obtained from domestic sources, such as timber, but are largely supplemented through imported waste paper. Indonesia’s paper industry requires approximately 10.7 million tons of raw materials annually, of which around 7.6 million tons are fulfilled through imports in the form of waste paper. These imports arrive in large quantities, often transported in thousands of containers. This study applied a normative legal research method, focusing on the analysis of legal norms and regulations related to waste import policies. The approach relies on secondary data, including legislation, legal doctrines, case law, and scholarly commentaries within the scope of Commercial (Economic) Law and Environmental Law. The findings indicate that the implementation of waste import policies still faces significant challenges. Issues such as the smuggling of hazardous and toxic waste, document falsification, and the mixing of dangerous waste with non-hazardous materials continue to occur. Furthermore, existing regulations are not sufficiently detailed or stringent in defining permissible waste types, contamination levels, and quality standards. Therefore, stricter and more comprehensive legal frameworks are necessary to ensure proper verification, prevent environmental harm, and regulate waste imports effectively, including provisions for acceptance or re-export of non-compliant materials